Response style, gender, and depressed mood : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Psychology - Madsen, Suzanne Mary (Massey University, 1998)
The present study was an attempt to replicate and extend the observational study reported by Nolen-Hoeksema, Morrow, and Fredrickson (1993). Nolen-Hoeksema et al. found support for Nolen-Hoeksema's 'response style' theory -- which explains the gender difference in depression rates as a byproduct of gender-specific styles of responding to depression (a ruminative style being associated with longer and more severe episodes of depression). Sixty-four students completed three initial pencil-and-paper measures and then tracked their naturally occurring depressed moods for thirty consecutive days via a 'Daily Emotion Report'. Participants recorded the characteristics of their depressed moods (e.g., severity and duration), their responses to these moods (e.g., type and effectiveness), and the characteristics of any event precipitating the mood (e.g., seriousness). Over the 30-day period, individuals showed a high consistency in response to depressed mood. However, contrary to Nolen-Hoeskema et al.'s findings, there were no sex differences in levels of depression nor in response styles to depressed mood. Of Nolen-Hoeksema's two response styles, distraction was used predominantly by respondents and 'distracters' tended to fare better than 'ruminators'. The number of initial ruminative and distractive responses and the initial severity of the moods at episode onset did not differ significantly over the month, nor did they prolong episodes. Regression analyses showed that severity of sadness was the most important and consistently significant predictor of the duration of depressed mood.
Keywords: Mental depression